The fragmentation of forest management: A case study of the Iraqis adoption of legal overlapping to climatic change and biological diversity regimes - Alsahlanee, Ali Sadik Thajb (2023)
The legacy of the fragmentation of international law has been transferred to its branches, particularly international environmental law. Forest management is a sector exhibited by massive separation of legal instruments on an international level, specifically those under climatic change and biological diversity regimes. The outcomes of such separation are overlapping and even a trade-off to achieve multiple objectives. This study identified these phenomena have reflected on Iraq‘s national level and, the extent to which the mitigation of climate policies on the forest sector in achieving the 2°C goal could subsequently have consequences on forest biodiversity and Sustainable Development Goals (SDGs) through fragmented legislation and the implementation of multiple policies on forest management. The mitigation policies for Iraq's Nationally Determined Contribution (INDC) pledge under the Paris Agreement in the land management and forest sector could have ramifications in a variety of sectors. However, such ramifications have seldom been investigated in Iraq, which also bears a trade-off and negativity to the people, food, and other diverse characteristics of land resources and forests. This study uses a qualitative approach by combining both doctrinal and socio-legal; including the implementation of face-to-face interviews. The primary data were texts of international conventions and enacted forest legislations in Iraq, as well as the national environmental data from reports of ministries and committees. Other primary data sources in this research included data acquired from three groups of people: university lecturers, ministry personnel and employers. The secondary data compromised of academic publications such as empirical investigations, books, and journals. The findings would aid policymakers and legislators in Iraq in formulating win-win policies and integrating mitigation policies with conservation management that do not harm the forest sector's biodiversity. The finding could also guide the policymakers and legislator in taking climate action towered achieving the global 2°C goal in the context of biodiversity and SDGs.